Macroeconomic Stability, Fiscal Policy and Taxation : National Development Strategy Croatia 2030 Policy Note - World Bank (World Bank, Washington, DC, 2021)
Croatia has made significant economic progress since independence, but the global financial crisis has exposed weaknesses in its economy and growth model. While growth has resumed in 2015, income convergence has been thrown back by the crisis and by the prolonged recession that followed and is currently proceeding only slowly. Low growth potential, deriving from low productivity growth, an ageing society, emigration, and a pace of capital accumulation lower than before the crisis, needs to be boosted for sustainable and reasonably rapid income convergence with the EU28. To this end, the export sector merits particular attention. Integration in global value chains and exposure to international competition would help to strengthen firm-level productivity, investment, and wages. Croatia has the smallest goods export sector among its peers in Central and Eastern Europe (CEE), and while exports of services are strong thanks to a vibrant tourism industry, the potential for productivity improvements there is limited. Fiscal policy will need to remain tight, as high public debt, to a significant extent denominated in foreign currency, needs to be reduced and fiscal space rebuilt. However, there is scope for using expenditure policies, for instance better targeting of social assistance, to increase incentives for labor force participation, which would help counter adverse demographic trends, reduce the need for fiscal transfers and increase the scope for raising public investment, and reduce inequality and poverty. Lastly, the effectiveness and efficiency of public sector service delivery across almost the entire public sector will need to be raised. This will also serve to make Croatia a more attractive destination for investments, which in turn would help boost output, reduce unemployment, and provide more revenue.